2021
DOI: 10.3389/fmars.2021.759067
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Analysis of Episodic Beach Erosion by Applying Storm Wave Scenarios to a Shoreline Response Model

Abstract: Recently, because of the influence of climate change on sea level change, there has been growing concern regarding the erosion of beaches, which play a role in reducing the damage caused by coastal disasters. However, despite these concerns, a comprehensive understanding of the morphodynamic relationship between hazard factors and beach erosion is still lacking. Therefore, in this study, a vulnerability analysis of beach erosion was conducted by applying the shoreline response model (SLRM) of bulk model type, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Lesht (1989) reported that the beach recovery factor was proportional to the settling velocity, median grain size, and transport coefficient, and was inversely proportional to the closure depth by applying the cross-shore sediment transport equation proposed by Hanson and Larson (2000). Kim et al (2021) verified the beach recovery factor correlates with the elapsed time from peak wave height to peak erosion by applying storm wave scenario to ODE (ordinary differential equation) model results. Recently, Lim et al (2022) presented research results that clarified the specific physical meaning of the beach recovery factor by introducing the concept of the horizontal behavior of suspended sediment.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Lesht (1989) reported that the beach recovery factor was proportional to the settling velocity, median grain size, and transport coefficient, and was inversely proportional to the closure depth by applying the cross-shore sediment transport equation proposed by Hanson and Larson (2000). Kim et al (2021) verified the beach recovery factor correlates with the elapsed time from peak wave height to peak erosion by applying storm wave scenario to ODE (ordinary differential equation) model results. Recently, Lim et al (2022) presented research results that clarified the specific physical meaning of the beach recovery factor by introducing the concept of the horizontal behavior of suspended sediment.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, Kim et al (2021) proposed a bulk response model of the shoreline by the horizontal behavior of suspended sediment. The governing equation of their proposed model showed the type of ODE type similar to that of the shoreline response model proposed by Miller and Dean (2004).…”
Section: Beach Recovery Factor In Shoreline Response Modelmentioning
confidence: 99%
See 3 more Smart Citations